A clinical study of the effects of cilnidipine and amlodipine in hypertensive patient focusing on pedal edema - Nidhi Uniyal; Vikaram Singh (International Journal of Medical Research and Review, 2016)
Introduction: Many Calcium channel blocker drugs for control of hypertension are available. New drug Cilinidipine is available and approved for treatment of hypertension. It acts by blocking both L-type and N-type voltage-dependent calcium channels. The neural N-type blockade leads to stoppage of the secretion of norepinephrine and it also depresses sympathetic nervous system activity. The aim of the study is to assess the effect of cilnidipine and amlodipine on hypertensive patient.Method: Clinidipine (n=50) and Amolodipine (n=50) were given once daily and BP was measured daily before and after the medicine in 100 hypertensive patients on OPD basis in GDMC, Dehradun.Result: Only 4 patients (n=50; 8%) in cilnidipine group developed edema within 10 days of therapy, while 32 patients (n=50, 64%) developed with edema within 10 days of treatment in amlodipine group.Conclusion: Cilnidipine is also associated with less incidences of pedal edema which is main complaint of patient. It controls BP better with less reflex tachycardia and decrease in morning surge.